2010
DOI: 10.1021/jp105358v
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of the Isomerization and Hydration Reactions of Acetaldehyde Oxide and Methyl Vinyl Carbonyl Oxide

Abstract: Alkene ozonolysis is a major source of hydroxyl radical (*OH), the most important oxidant in the troposphere. Previous experimental and computational work suggests that for many alkenes the measured *OH yields should be attributed to the combined impact of both chemically activated and thermalized syn-alkyl Criegee intermediates (CIs), even though the thermalized CI should be susceptible to trapping by molecules such as water. We have used RRKM/master equation and variational transition state theory calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
200
8
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(228 citation statements)
references
References 120 publications
(255 reference statements)
18
200
8
2
Order By: Relevance
“…with the terminal oxygen of the carbonyl oxide moiety on the same side as a hydrogen group) react relatively fast with H 2 O. This difference has been predicted theoretically (Kuwata et al, 2010;Anglada et al, 2011) and was subsequently confirmed in recent experiments (Taatjes et al, 2013; for the two CH 3 CHOO conformers. Additionally, it has been predicted theoretically (Vereecken et al, 2012) that the relative reaction rate constants for the water dimer vs. water monomer, k(SCI + (H 2 O) 2 )/k(SCI + H 2 O) of larger SCIs (except syn-CH 3 CHOO) will be over 70 times smaller than that for CH 2 OO, suggesting that reaction with the water dimer is unlikely to be the dominant fate for these SCIs under atmospheric conditions.…”
Section: Stabilised Criegee Intermediate Kineticssupporting
confidence: 61%
See 1 more Smart Citation
“…with the terminal oxygen of the carbonyl oxide moiety on the same side as a hydrogen group) react relatively fast with H 2 O. This difference has been predicted theoretically (Kuwata et al, 2010;Anglada et al, 2011) and was subsequently confirmed in recent experiments (Taatjes et al, 2013; for the two CH 3 CHOO conformers. Additionally, it has been predicted theoretically (Vereecken et al, 2012) that the relative reaction rate constants for the water dimer vs. water monomer, k(SCI + (H 2 O) 2 )/k(SCI + H 2 O) of larger SCIs (except syn-CH 3 CHOO) will be over 70 times smaller than that for CH 2 OO, suggesting that reaction with the water dimer is unlikely to be the dominant fate for these SCIs under atmospheric conditions.…”
Section: Stabilised Criegee Intermediate Kineticssupporting
confidence: 61%
“…Chao et al, 2015;Lewis et al, 2015) have demonstrated a quadratic dependence of CH 2 OO loss on [H 2 O], suggesting a dominant role for the water dimer, (H 2 O) 2 , in CH 2 OO loss at typical atmospheric boundary layer H 2 O concentrations. For larger SCIs, both experimental (Taatjes et al, 2013;Newland et al, 2015) and theoretical (Kuwata et al, 2010;Anglada et al, 2011) studies have shown that their kinetics, in particular reaction with water, are highly structure dependent. syn-SCIs (i.e.…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 99%
“…1) does. Quantum-chemical investigations (25)(26)(27) as well as studies of alkene ozonolysis (20,28) SO 2 , these CIs may accumulate to higher concentrations and have higher probability to oxidize atmospheric SO 2 . Table 1 shows selected rate coefficients for relevant CI reactions and the effective first-order decay rate coefficients (k eff ) of small CIs under an atmospheric condition.…”
mentioning
confidence: 99%
“…Quantum-chemistry (25)(26)(27) calculations predicted that the antiform of CIs (CIs with R 1 = H in Fig. 1, including CH 2 OO) react with water vapor very quickly and that the syn-form of CIs (CIs with R 1 ≠ H in Fig.…”
mentioning
confidence: 99%
“…The subsequent reactions of sCIs produce both carbonyl products and non-carbonyl products such as hydroperoxides. The syn and anti conformers of CIs and sCI can have substantially different reactivities (Kuwata et al, 2010;Anglada et al, 2011), with syn conformers more likely to decompose unimolecularly, possibly through a vinyl hydroperoxide intermediate .…”
mentioning
confidence: 99%